RESPONS PEMBERIAN JENIS PUPUK KOTORAN HEWAN DAN PESTISIDA NABATI TERHADAP SERANGAN HAMA DALAM MENINGKATKAN PRODUKSI TANAMAN BAYAM MERAH (Amaranthus dubius) SECARA ORGANIK - Muhammad Bahrul Ulum; Istiqomah Istiqomah; Mariyatul Qibtiyah (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Red spinach is one of the vegetable horticultural crops used for its leaves. Red spinach cultivation generally uses chemical fertilizers and pesticides because the impact is felt more quickly, but the use of chemical fertilizers and pesticides causes a decrease in productivity. One of the efforts to improve the quality and productivity of red spinach plants can be done by adding organic materials, such as substitutes for chemical fertilizers and pesticides, namely animal manure fertilizers and vegetable pesticides. The purpose of the study was to determine the response of giving types of organic fertilizers and vegetable pesticides to the production of red spinach plants. A Factorial Randomized Group Design (RAK) method, which is divided into three levels and has two factors, was used in this study. Types of animal manure fertilizer and plant-based pesticides were the first and second factors. Types of animal manure fertilizers used: cow manure, vermicompost fertilizer and guano fertilizer. Vegetable pesticides used: biomoxa, neem oil extract and MS. Fisher's variance (F test at 5% level) was used to analyze the observation data. If significant differences were found, then the Least Significant Difference Test (BNT 5%) was continued. The best results in this study were obtained in the treatment of cow manure and vegetable pesticide Neem oil extract.